The Application Of “IMPROVE’ Learning Model Toward Information And Communication Technology Subject To Improve Critical Thinking Ability And Student Learning Outcomes in Grade VIII B1 Of SMP Negeri 4 Singaraja In Academic Year 2011/2012 - Ni Nengah Dwi Apriani (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This Classroom Action Research was aimed at: 1) increasing students' critical thinking skills through IMPROVE learning model, 2) improving students’ learning outcomes through IMPROVE learning model, 3) describing the response of students to the IMPROVE learning model. This study was a Class Action Research (PTK), the place of the research was in SMP Negeri 4 Singaraja and was implemented in semester 2 in academic year 2011/2012.  The subjects of research were the students in grade VIII B1 of SMP Negeri 4 Singaraja in Academic Year 2011/2012 with the objects of research were in the form of critical thinking skills and student learning outcomes. Data of the critical thinking skills were collected using observation sheets, for student learning outcomes data were collected through the learning result test, while for the students’ response data retrieved using the enclosed questionnaire. The data collected was analyzed using descriptive analysis.          The result of the research showed that: (1) the increasing in the average students' critical thinking skills in information and communication technology subject from cycle I was 9,66 with a high qualification became 12,41 with a very high qualification in cycle II, (2) The student learning outcomes have increased from cycle I at 73,5 became 89,83 in cycle II. The classical completeness in cycle I at 68,75% increased to 100% cycle II, (3) The response of students to the IMPROVE learning models in ICT subjects were at a very positive qualification with an average of 49.97